Metformin Versus Insulin in the Managment of Gestational Diabetes Mellitus - Nuha Muhsen; Sajda Al-Rubai; Huda Qahtan (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Insulin and metformin have been used extensively in the management of gestational diabetes mellitus (GDM).Insulin has been the primary medical treatment if maternal glucose targets are not achieved by dietary therapy.Insulin is safe for the fetus, because it does not normally cross the placenta. oral antidiabetic agents, glibenclamideand metformin are the most studied agents to treat GDM patients.Objective: To examine If oral metformln Is as effective as Insulin ln the prevention of fetal macrosomy lnpregnancies complicated with gestational diabetes mellitus.Method: This study is an open -labeled prospective randomized controlled study that was carried out in Basramaternity-outpatient clinics in the tertiary level hospital ln Basra. One hundred women with GDM who didnot attain euglycaemia with diet participated. Women were randomized to therapy with insulin n= 50 or oralmetformin n=50. Incidence of macrosomia in infants and neonatal morbidity was measured.Results: There were no statistically significant differences tn the incidence of macrosomia (16°/o versus 20°/o), and neonatal morbidity between insulin and metformtn group. Around 15 (30°/o) of the metformin treatedwomen needed supplemental insulin. They were more obese,(36.2 versus 30.6) kg/m2 bad higher fasting bloodglucose level (7.4mmol/L versus 6.1 mmol/L) and needed medical treatment for GDM earlier ( 27 versus 32 wks )than women who were normoglycemic with metformin alone. There was a tendency to a higher rate of caesareansections in the metformin group than in the insulin group.Conclusion: Metformin seems to be suitable for the prevention of fetal macrosomia , especially in lean or moderatelyoverweight women developing GDM in late pregnancy Women with considerable obesity, high fasting bloodglucose and an early need for pharmacological treatment may be more suitable for insulin therapy.